TOWARDS THE ALGORITHMIC BANKING MODEL: REVITALIZING PAULO FREIRE’S CRITICAL PEDAGOGY IN THE ERA OF AI-MEDIATED EDUCATION (International Journal of Cultural and Social Science, 2026)
The education system worldwide mostly witnessed an aggregate approach considering the generalized demand of public education ignoring the individualized learning need and critical reflection into it. This results in transferring obsolete and static knowledge to the stakeholders making them nugatory depositors in a banking system. Paulo Freire’s groundbreaking theory of oppression in pedagogical approach had justified the notion of banking knowledge system where a dominant institutional ideology holds the power to disburse a conventional approach of curriculum transaction that inhibits the learners to inculcate critical consciousness. This type of education had failed to trigger the critical and reflective inquiry within the learners leading to passive receptors among learners. In the current educational scenario, AI-driven automated learning management system with its capability to produce diverse range content, assessment and data surveillance based predictive analytics revitalizes the banking concepts of knowledge while turning the learners into mere data points creating a new form of oppression and control in educational context. Though there are possible risks associated with it, AI’s enormous prospective to recapitulate the Freire’s philosophy of problem posing education, praxis, conscientization, dialogue practices into fostering critical AI literacy among stakeholders, growing human- AI interaction transforms AI as a tool for pedagogical liberation rather than oppression. This study aimed to propose a revived Freirean framework redefining the possible human-AI partnership in balancing the newly formed algorithmic educational model. A qualitative study of critical hermeneutical interpretation was used to redefine the existing theory to provide subjective meanings within the contexts. This approach simultaneously adjoins and critiques the traditional method to reinterpret newer algorithmic banking model of education in AI-embedded learning environment. This method also tried to elucidate AI’s enormous role in democratizing education with its tendencies towards automated knowledge oppression. This critical interpretative study also highlighted how critical pedagogy can foster a futuristic education where the automated intelligence serves pedagogical liberation centering human learning needs in its core.